Adaptation and validity of the Type D personality scale (DS-14) in a Mexican sample - Juárez-García, Arturo (2018)
The goal of this study was to explore the psychometric properties of a Spanish version of the Type D Personality Scale (DS-14) in a sample of Mexican participants (n = 702). The scale was evaluated through a non-parametric approach based on Mokken scaling. Moreover, confirmatory factor analyses were performed using the weighted least squares mean and variance (WLSMV) method, internal consistency estimation with omega coefficient (ω), measurement invariance by gender, and convergent validity with mental health measures (MBI = burnout, GHQ = depression, sleep disorders, social dysfunction, and somatic symptoms), and controlling job stressors (JCQ = job demands and job control). The results showed low to moderate partial correlations in DS-14 items concerning the mental health scores, and acceptable reliability rates (ω = .62-.86). Measurement invariance between men and women was found, and the original two-factor structure showed satisfactory adjustment indices (CFI = .97, RMSEA = .04, SRMR = .05). Furthermore, the viability of a one-dimensional structure, which needs future replicability studies, was glimpsed particularly in the 9-item version (CFI = .99, RMSEA = .04, SRMR = .04). It is concluded that the DS-14 scale generates valid and reliable scores, and these findings and implications are discussed for further research.